Euro money market trading during times of crisis - Falko Fecht; Stefan Reitz (Kiel Institute for the World Economy (IfW), 2015)
This paper uses the order book for 2007 and 2008 of a key Euro area market maker in the unsecured money market to estimate a stylized pricing model which explicitly accounts for the over - the - counter structure and the unsecured nature of these transactions. The empirical results suggest that the market maker learns from order flow to update her beliefs about the fundamental value of the overnight rate, but this information aggregation via order flow was increasingly hampered as the crisis unfolded. In addition, order size was also used to infer the unobservable component of a counterparty's credit risk.
Keywords: G15; E43; C32; 330; Euro money market; financial crisis; market microstructure; pricing behavior